A Virtual Impedance Enhancement Based Transformer-Less Active EMI Filter for Conducted EMI Suppression in Power Converters - Zhang, Zhe; Bazzi, Ali M. (IEEE transactions on power electronics, 2022)
Due to the successive switching actions in a power electronic system, considerable conducted electromagnetic interference (EMI) is generated. This has been a major concern in designing power converters, which requires additional EMI filtering efforts. Passive EMI filters are the most common solutions to EMI reduction but usually consume a large portion of the volume as well as weight in power converters. Active EMI filters (AEFs) or hybrid EMI filters (HEFs) are considered best candidates over traditional passive EMI filters to achieve higher power density in power converters. The utilization of current transformer to sense or to compensate the EMI noise can increase the volume of an AEF. In this article, a transformer-less AEF, sprung from the concept of virtual impedance enhancement, is proposed. The proposed design features feedforward control with current-sensing-voltage-compensating. The operation principle of the proposed AEF is thoroughly introduced, and its performance is evaluated through simulations and experiments. Experimental results with an ac-dc power converter and a dc-ac inverter show that the proposed AEF can be generally applied to reduce conducted EMI on either ac or dc power lines.